2018
DOI: 10.4314/jfas.v9i5s.57
|View full text |Cite
|
Sign up to set email alerts
|

Al-Quran ontology based on knowledge themes

Abstract: Islamic knowledge is gathered through the understanding the Al-Quran. It requires ontology which can capture the knowledge and present it in a machine readable structured. However, current ontology approaches is irrelevant and inaccuracy in producing true concepts of Al-Quran knowledge, because it used traditional methods that only define the concepts of knowledge without connecting to a related theme of knowledge. The themes of knowledge are important to provide true meaning and explanation of Al-Quran knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The ontology approach is also adopted by Ta'a et al [39] but it is more user friendly. Instead of performing some syntax based queries, a graphical user interface allows user to select a particular topic or theme and two sub themes from drop down menus.…”
Section: H Knowledge Extraction and Qur'anic Nlpmentioning
confidence: 99%
See 1 more Smart Citation
“…The ontology approach is also adopted by Ta'a et al [39] but it is more user friendly. Instead of performing some syntax based queries, a graphical user interface allows user to select a particular topic or theme and two sub themes from drop down menus.…”
Section: H Knowledge Extraction and Qur'anic Nlpmentioning
confidence: 99%
“…Protégé-OWL itself is developed in Java. This technology has been utilized by Ta'a et al [39] in development of ontology for the Qur'an. Since it is an open source tool, it can be helpful in developing conceptual search system based on ontology.…”
Section: E Tools For Ontologymentioning
confidence: 99%
“…Ta'a et al [39] also developed theme based ontology named as Al-Quran to perform the semantic queries. Ontology is developed using Protégé-OWL.…”
Section: Ontology Based Technologiesmentioning
confidence: 99%
“…In the research executed by Ta'a et al the researchers demonstrated the ontology of Al-Quran and implemented a method used for retrieving the Quranic knowledge via the semantic search approach (43,44). On the other hand, a research by Almeida, Roche, and Costa (45) and Almeida and Costa (46) emphasised on the significance of the Islamic artefacts and archaeology in the built ontology, namely OntoAndalus.…”
Section: Related Workmentioning
confidence: 99%